The Influence of Students' Creativity to Construct Sentences toward Their Speaking Skill - Mukminatus Zuhriyah; Ria Kamilah Agustina; Maskhurin Fajarina (UIN Salatiga, 2018)
One of the obligated English materials studied by all students of Indonesian universities is speaking English because English is one of the international languages used to communicate in the world. Moreover, many work fields offered from abroad to Indonesian scholars obligate them to speak English well. Having capability to speak English well is not an easy task. There are some factors influencing the ability of speaking. One of the factors is creativity. Therefore, this research is concerned on investigating the influence of students’ creativity to create sentences toward their speaking skill. This article only discusses one of the three objectives of this quasi experimental research. It is whether or not the students having high creativity have high speaking skill. The data of this research consisted of the scores of creativity test and speaking test. The data of speaking scores were categorized into two, scores of the students having high and low creativity. After those data were normal and homogeneous, then, analyzed using F-test ANOVA. The difference between rows is significant because Fo between rows (1125.64) is higher than Ft (4.11) at the level of significance α= 0.05. The mean score of B1 (78.9) is higher than that of B2 (60.85), it can be said that the speaking skill of students having high creativity is higher than those having low creativity. Thus, it can be concluded that students’ creativity influences their speaking skill.Keywords: Influence; Students’ Creativity; Speaking Skill